Clinicolaboratory characteristics and 1-year survival among group 1 pulmonary hypertension in a university hospital - Mostafa K. Ahmed; Ali M. Tohamy; Mostafa H. Ali; Mohamed I. Seedik; Safa M. Wafy (The Egyptian Journal of Bronchology)
Abstract Background Pulmonary arterial hypertension is a life-threatening disorder of the pulmonary vascular system that can lead to right-sided heart failure, respiratory failure, and death. Still, more knowledge is needed to understand this complex disease. The study objective is to evaluate the clinicolaboratory characteristics of group 1 pulmonary hypertension patients and their survival in the Assiut University pulmonary hypertension unit throughout the study time. Patients and methods Consecutive patients were referred to the Assiut University Chest Department Pulmonary Hypertension unit in collaboration with the cardiology department for diagnosis and management. Patients were diagnosed as group 1 pulmonary hypertension (PH) included in the study. Patient demographic data, clinical presentation, electrocardiography, laboratory data, and invasive and noninvasive hemodynamics at presentation were recorded. The patients were followed through the study time to identify their survival. Results Out of 40 patients referred to the pulmonary hypertension unit throughout the study period, 29 patients have group 1 PH and were included. Their mean age was 44.10 ± 15.14 years, most of them were females (86.2%), 44.8% of patients presented with WHO functional class II, 48.3% of patients with FC III, and 6.9% of patients with FC IV. The mean 6 min walking distance was 256.97 ± 89.46 m. Pulmonary artery catheterization hemodynamic parameters were mean pulmonary artery pressure 52.48 ± 18.24 mmHg, pulmonary vascular resistance 13.32 ± 7.31 WU, cardiac index 2.32 ± 0.83 L/min/m2, and mixed venous oxygen saturation 59.6 ± 7%. The mean follow-up duration is 12.6 ± 8.8 months, and their survival at the end of study time was 82.35%. Serum uric acid, pulmonary vascular resistance, pulmonary artery systolic pressure, and age are predictors of disease progression and mortality. Conclusion Group 1 pulmonary hypertension is an uncommon complex disease with a difficult early diagnosis. Its clinical presentation varies from insidious breathlessness, syncope, palpitation, and obvious right heart failure. Some factors as serum uric acid, pulmonary vascular resistance, pulmonary artery systolic pressure, and age are associated with prognosis. One-year survival was 82.35%. Trial registration ClinicalTrials.gov ID: NCT0479145.